The estimation of errors in calculated terrain corrections in the Tatra Mountains - ZAHOREC, Pavol; PAŠTEKA, Roman; PAPČO, Juraj (Contributions to Geophysics and Geodesy, 2010)
In general, calculation of terrain corrections can be a substantial source of errors in evaluating Bouguer anomalies, especially in rugged mountainous areas like the Tatra Mountains where we also get the largest values of the terrain corrections as such. It is then natural that analysis of their calculations in this area can shed light on the magnitude of correction-related errors within the whole Slovak territory. In the framework of our analysis we have estimated the effect of different computing approaches as well as the influence of accuracy of the inputs, i.e. the heights and positions of the measuring points, together with the used digital terrain models. For the sake of testing the computer programs which are currently in use, we have also substituted the real terrain by synthetic topography. We found that among the concerned constituents the most important factor is the used digital terrain model and its accuracy. The possible model-caused errors can exceed 10 mGal in the Tatra Mountains (for the density of 2.67 g.cm−3).